Prolactin level correction in restoration of menstrual cycle in obese women - T.F. Tatarchuk; N.V. Kosei; S.I. Reheda; M.I. Hlamazda; I.M. Shakalo (Publishing House TRILIST, 2021)
Obesity is a common problem among women of reproductive age. There are data from clinical and experimental studies indicating the role of hyperprolactinemia in the development of metabolic syndrome, as well as the metabolic benefits of treating hyperprolactinemia. Research objective: to evaluate the clinical efficacy of Vitex Agnus Castus standardized extract on hormonal and metabolic status in women with menstrual cycle disorders and obesity. Materials and methods. 60 women aged 19 to 35 years with obesity and menstrual cycle disorders with laboratory-confirmed insulin resistance and prolactin near the upper limit of the reference values or was slight increase were examined. All the patients were given recommendations for lifestyle modification. 30 of them, who formed the main group, received Cyclodynon. 30 patients of the control group were not prescribed Cyclodynon therapy. Results. At the end of the treatment, the menstrual cycle was normalized in 93.3% patients of the main group, and in 66.3% patients of the control group (p < 0.05). Ovulation signs were detected in 86.67% women of the main group and only in 30.0% women of the control group (p < 0.05). The mean prolactin value and the HOMA index were significantly lower in the main group; prolactin level did not exceed the physiological values in 86.67% women in the main group after 6 months, and in 40.0% of the control group, p < 0.05. There was a decrease in body mass index and waist/hip circumference ratio in patients of the studied groups; the dynamics was slightly higher in the main group but did not differ significantly. Conclusions. Cyclodynon is effective for the treatment of menstrual cycle disorders and metabolic disorders in women with obesity and metabolic syndrome. Good tolerability, absence of side effects, and sufficient efficacy of Cyclodynon allow it to be recommended as the drug of choice in patients with prolactin levels near the upper limit of the reference values or a slight increase of it and in patients with intolerance to synthetic dopamine agonists.